PENGARUH KARAKTERISTIK INDIVIDU DAN SAFETY LEADERSHIP DENGAN MOTIVASI KERJA TERHADAP SAFETY PERFORMANCE PEKERJA TAMBANG - Azis, Asti Hardianti; Arifuddin, Nur Fitiyani; H, Ayu Wulandari Pertiwi; Ahmad, Muh. Fandi (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
Safety performance is work behaviour that is relevant to safety which can be conceptualized the same as other work behaviour which is the result of work. In order to achieve a good safety performance, a commitment to good occupational safety and health management is required from all components in the company. The success of occupational health and safety management in an organization is closely related to roles of management and employees. This study aims to determine the effect of safety leadership and individual characteristics on safety performance. A mix methods research that is qualitative study by conducting indepth interviews and quantitative study with cross sectional design. Interviews were conducted on 65 workers who were drawn based on the multistage random sampling of 199 workers in PT. Masmindo Dwi Area. To understand the effect of safety leadership and individual characteristics on safety performance, data were analyzed using path analysis with smartPLS application. The results of this study indicate that there is a direct effect of safety leadership on safety performance (p=0,003) and there is an indirect influence of the level of education (p=0,042) and attitudes (p=0,018) towards safety performance. Meanwhile, there is no direct and indirect effect of age and years of service on safety performance. Writer suggest that PT. Masmindo Dwi Area should adapt the work physical conditions and abilities of workers, increase the quantity and quality of training for workers related to safety issues and to hold safety award program.